DIFFERENCES IN THE QUALITY OF SLEEP ON HANDGRIP STRENGTH IN THE ELDERLY AT POSYANDU LANSIA YOGYAKARTA - Ghea De Silva; Mustofa Mustofa; Rizak Tiara Yusan (Mandala Of Health, 2021)
Decreased sleep quality in the elderly can affect protein formation and maintenance of muscle mass. Decreased muscle function in the elderly can have an impact on daily activities and can affect morbidity and mortality. A simple measurement of overall muscle strength can be done by testing handgrip strength using a handgrip dynamometer. Several recent studies have shown a close relationship between sleep quality and muscle strength. This study aims to determine differences in the value of hand grip strength according to sleep quality in the elderly population at the Yogyakarta elderly Posyandu. The research was conducted with cross sectional method. The research subjects were elderly posyandu participants in the city of Yogyakarta with a total of 255. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Handgrip strength is measured with a Takei Handgrip Dynamometer. Of the 255 research subjects, there were 146 (57.3%) elderly people with good sleep quality and 109 (42.7%) elderly people with poor sleep quality. The average value of hand grip strength in the elderly group with good sleep quality was 22.64 kg and the average value of hand grip strength in the elderly group with poor sleep quality was 14.28 kg. With the Mann Whitney test, statistically significant results were obtained with p <0.001. This study shows that there is a significant difference in the value of hand grip strength between the elderly with good sleep quality and the elderly with poor sleep quality with a mean difference in hand grip strength value of 8.36 kg where the minimum difference that is considered clinically significant is 6.5 kg